On Ukrainian Translations of Marina Tsvetaeva’s Poetry - Григорьева, Ирина (Didactics of the Russian language and the problems of translation for a foreign audience, 2020)
The article reflects on the reasons for the relatively small representation of Marina Tsvetaeva’s poetry in Ukrainian context. The examples of successful and unsuccessful translations of one of the most difficult poems (in Russian Niepodrazhaemo lzhot zhyzn) are shown and their comparative analysis is performed.